(3GdOhd GdefbWYIs - (3Ydj Hf XGaQ Hf MSjf GdCROj GdNRQLj, CHh GdMSf LeGd GdOjf,J (B613 (3g` s
(3ChdgG (B:s
(3jHJOF ef CKfGA CNHGQ GdOhdI GdMeOGfjI , Ke CNHGQ GdOhdI GdSGLjI HGdLHGd , hCNHGQ GdOhdI GdWhdhfjI , hCNHGQ GdOhdI GdaGWejI HCaQjbjI heUQ hGdTGe Gdjef s
(3BNQgG (B:s
(3jfJgi Edi SfI (B575 s
(3hGdejcQhajde Hg Jdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B113s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B63 s
Keywords: (3GdJGQjNs